AKAD MUDLARABAH DALAM PRODUK PEMBIAYAAN BANK SYARIAH - Arifah, Risma Nur (De Jure: Jurnal Hukum dan Syari'ah, 2011)
Bank syariah start initiated in Indonesia in the early period of the 1980s. But as an institution in the international sphere has begun to bloom, the emergence of Islamic banking institutions would have been preceded by intensive study of Islamic economic experts on the application of Islamic teachings in the formation of these institutions. The author examines how the concept of capital development based on mudlarabah financing practices and the implementation of the financing products in the system of Islamic banking operation in Indonesia.Bank syariah mulai digagas di Indonesia pada awal periode 1980-an. Namun sebagai sebuah lembaga yang dalam lingkup internasional sudah mulai marak, kemunculan lembaga perbankan Islam tentu sudah didahului dengan kajian intensif dari para pakar ekonomi Islam tentang aplikasi ajaran Islam dalam pembentukan lembaga tersebut. Penulis meneliti bagaimana konsep pengembangan modal berdasarkan praktek pembiayaan mudlarabah serta penerapannya dalam produk pembiayaan dalam sistem operasional bank Islam di Indonesia.